2012
DOI: 10.1074/jbc.m112.415786
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Critical Residues in the Channel Domain of Inositol Trisphosphate Receptors

Abstract: Background: Mutagenesis was used to gain insights into the structure/function of IP 3 R channels. Results: Only 5 of 22 residues mutated proved essential for channel function. Conclusion: We propose that Ile-2588 and Ile-2589 are at the channel gate. Arg-2596, His-2630, and His-2635 maintain the structure of the pore and facilitate contacts critical for channel gating. Significance: A revised model of channel gating is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…These studies provide a structural basis to explain our data whereby the expressed fragmented receptor can associate through non-covalent interactions in vivo. Mutagenesis of key residues in the suppressor domain and the transmembrane linker also indicates that these interactions are pivotally important for transducing the conformational change induced by IP 3 binding to opening of the pore (5,(52)(53)(54). These data indicate that a conformational change transmitted through the entire linear peptide sequence of the cytosolic domain of the protein is not necessary for gating.…”
Section: Discussionmentioning
confidence: 59%
“…These studies provide a structural basis to explain our data whereby the expressed fragmented receptor can associate through non-covalent interactions in vivo. Mutagenesis of key residues in the suppressor domain and the transmembrane linker also indicates that these interactions are pivotally important for transducing the conformational change induced by IP 3 binding to opening of the pore (5,(52)(53)(54). These data indicate that a conformational change transmitted through the entire linear peptide sequence of the cytosolic domain of the protein is not necessary for gating.…”
Section: Discussionmentioning
confidence: 59%
“…While modulation of the InsP 3 R channel function has not been investigated regarding its sensitivity to Zn 2+ , this domain may have a role in coordinating metals that influence channel gating. Mutational studies of the C2H2 residues were shown to either inhibit (Cys2611Ser, Cys2614Ser, His2636Ala) or completely abolish (His2631Ala) channel function, indicating that the LNK domain is positioned to be a crucial structural component for allosteric modulation of channel gating 21,32 .…”
Section: Gating Via C- and N-terminal Couplingmentioning
confidence: 99%
“…Similar to residues in the LBD and selectivity filter, residue I2550 is also associated with multiple diseases as mutation I2550N is causative for pontocerebellar hypoplasia (PCH), while mutation I2550T is causative for SCA29 (Zambonin et al, 2017, van Dijk et al, 2017). The I2550 residue has been previously identified as potentially structurally significant as it may serve as a constriction site in the channel pore (Baker et al, 2017, Fan et al, 2015, Bhanumathy et al, 2012). Substitution of the highly conserved, hydrophobic Ile, by either Thr or Asn, would likely disrupt the TM domain and affect Ca 2+ signaling.…”
Section: Ip3r Mutations Associated With Human Disease By Domain: Mutamentioning
confidence: 99%